Pliocene benthic foraminifera stable isotopes values from Shatsky Rise and Pacific Ocean - Heather L Ford; Natalie J Burls; Peter Jacobs; Alexandra Jahn; Rocio P Caballero-Gill; David A Hodell; Alexey Fedorov (PANGAEA, 2022)
Benthic foraminifera stable isotopes values from Shatsky Rise 1209 and 1210. A synthesis of benthic foraminifera d13C values from the mid-Pliocene warm period and early Pliocene and OC3 products pre-Industrial water column d13C and Late Holocene core top benthic foraminifera d13C.